Pengaruh Marketing Mix, User Experience dan Brand Equity terhadap Customer Retention pada Perusahaan Redbus Indonesia - Deni Rahman; Nora Andira Brabo; Heni Iswati; Sandra Agustina; Siska Margaret Purba (Syntax Corporation, 2023)
This study aims to partially or simultaneously determine the Effect of Marketing Mix, User Experience, and Brand Equity on Customer Retention in Redbus Indonesia Company. Research methods used quantitative methods. The sampling method uses the purposive sampling method with a sample of 100 people. Data analysis techniques use descriptive statistical analysis and inferential statistics. This study was conducted using multiple linear regression method assisted by SPSS version 25 and Microsoft Excel 2016 program. The results showed that (1) There is an influence of Marketing Mix on Customer Retention. (2) There is an influence of User Experience on Customer Retention. (3) There is an influence of Brand Equity on Customer Retention. (4) There is an influence of Marketing Mix, User Experience, and Brand Equity on Customer Retention. The magnitude of the effect is 61.6% with the multiple regression equation Y = 25.793 + 0.216X1 + 0.329 X2 + 0.364 X3. This means that if the Marketing Mix, User Experience, and Brand Equity increase, it will increase Customer Retention, and vice versa if the Marketing Mix, User Experience, and Brand Equity decrease, it will decrease Customer Retention.